Stepping up in harmony: Achieving cluster school excellence (CSE) Status for Non-CSE Malaysian secondary schools - Bhattacharyya, E. (Universiti Putra Malaysia, 2014)
This paper proposes how aspiring non-CSE secondary schools can be on a par with CSE secondary schools through implementing school-based management (SBM). Though Malaysia aims to provide quality education for all children and produce quality human capital for the nation as envisioned in its Education Development Master Plan (EDMP) 2006-2010 through the CSE merit system, of date, only 1 of Malaysian schools have been identified as holding CSE status (Ismail & Abdullah, 2011; Malaklolunthu & Shamsudin, 2011). The percentage of CSE schools can be increased if more non-CSE secondary schools are groomed to meet the CSE requirements. For the purpose of this study, the researchers reviewed journal articles on SBM, and provide some insights on the challenges of implementing SBM. The research identified that non-CSE secondary schools have to overcome three challenges of SBM, namely, programme, participation and support to achieve CSE status. Â© Universiti Putra Malaysia Press.